CONSUMER PREFERENCE ANALYSIS OF NEW COMPLEMENTARY ORGANIC FOOD PRODUCTS - Nabila Ratna Kusumaningrum; Elisa Anggraeni; Budi Agus Pranoto (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
XYZ Fruit Puree is one of complementary food products developed by Company X. A marketing plan toexpand the market of the product is considered by developing new product variants, namely XYZ Organic FruitPuree. The plan is done by providing new price offers and changing the target market from upper Social EconomicStatus (SES) into middle to upper. This study aimed to evaluate consumer’s acceptance, purchase intention, andpreference toward XYZ Fruit Puree and XYZ Organic Fruit Puree product concepts. Non-parametric tests ofWilcoxon signed-rank test and Mann-Whitney test were used for data analysis in this study to compare thepreference of total samples and each sample groups differentiated by its social economic status and usership. Theresult showed that XYZ Organic Fruit Puree concept was more preferred by all types of consumers in aspects ofoverall liking, uniqueness, intention to buy, and preferential intention. However, if price was taken intoconsideration, intention to buy for XYZ Fruit Puree concept was significantly greater than the XYZ Organic FruitPuree concept. The recommendations given were the price of XYZ Organic Fruit Puree can be adjusted to be moreacceptable to consumers as well as increasing consumer trust in product safety.Keywords: consumer preferences, new product development, purchase